Music in Indie video games: a composer's perspective on musical approaches and practices - Harbour, Tim (My University, 2016)
In this part-written, part-composed creative research project I consider the music of ‘indie’ video games, specifically exploring some of the myriad dynamic compositional approaches in this particular category of game development. In my written work I analyse three indie video games – Braid (2008), Fez (2012) and Journey (2012) – each of which use unique methods to apply music dynamically. I use interviews with the games’ creators, as well as close analysis and transcription of significant sections of each video game, in order to reveal how music is used to provide the player with a more immersive, satisfying, and involving gaming experience. I also consider the use of ambient music in indie video games, a common feature of a large number of contemporary games, weighing up its merits and limitations. Musical concepts and compositional approaches raised in my written work have informed the portfolio of compositions submitted for this degree, and, similarly, my creative work has informed my analytical research. My creative work explores, amongst other aspects, indeterminate form, ambient music, and ways of ‘looping’ material in the creation of unrepeatable structures. This thesis also considers music which functions narratively in games – a function that might necessitate a greater degree of musical linearity — and how this musical role might be incompatible with the demands of interactivity. After briefly introducing the concepts dealt with across this thesis in Chapter 1, Chapters 2 to 4 take the form of case studies of the indie games mentioned above, with each chapter tackling unique challenges that game composers face when writing music for non-linear games, by which I mean games structured so that not all players will experience the content in the same order due to player agency. More specifically, Chapter 2 deals with the game Braid and its use of pre-composed, licensed music and how the game’s developer applies this music dynamically to the game. Chapter 3 deals with Fez and its mainly adaptive musical approach, its built-in software music engine, ‘Fezzer’, which allows for a composer to input and manipulate musical loops in the game, and nostalgia in indie video game aesthetics. Chapter 4 centres on the video game Journey and on how autonomous, ‘narrative’ music in video games might be seen to exist in opposition to music’s ability to be truly dynamic. Finally, Chapter 5 reflects on my own creative work for this thesis; how concepts from the case studies have informed my creative work and vice versa.
A thesis submitted to the Faculty of Humanities, University of Witwatersrand, Johannesburg, in fulfilment of the requirements for the Degree of Master of Music Johannesburg, 2016
Keywords: Video game music; Video game music--Analysis, appreciation; Computer game music; Video game music--Writing and publishing; Composition (Music)